Endotoxin testing of a wound debridement device containing medicinal Lucilia sericata larvae - Pickles, S.F.; Pritchard, David I. (Wiley, 2017)
Alimentary products of medicinal Lucilia sericata larvae are studied to determine their mechanisms of action, particularly in the contexts of wound debridement and disinfection. Furthermore, the larvae can be applied to patients in contained devices, such as the BioBag (BioMonde). Here, we tested the materials and larval content of the most commonly used BioBag (the “BB-50”) to explore the possibility that endotoxins may be contributing to the bio-activity of the product, given that endotoxins are potent stimulants of cellular activation. Using standardised protocols to collect larval alimentary products (LAP), we proceeded to determine residual endotoxin levels in LAP derived from the BioBag, before and after the neutralisation of interfering enzymatic activity. The BB-50 device and its associated larval content was not a significant source of LPS activity. However, it is clear from these experiments that a failure to remove the confounding serine proteinase activity would have resulted in spuriously high and erroneous results. The residual LPS levels detected are unlikely to be active in wound healing assays, following cross-referencing to publications where LPS at much higher levels has been shown to have positive and negative effects on processes associated with wound repair and tissue regeneration.